Discover the answers to your questions at Westonci.ca, where experts share their knowledge and insights with you. Connect with a community of experts ready to help you find solutions to your questions quickly and accurately. Join our Q&A platform to connect with experts dedicated to providing accurate answers to your questions in various fields.
Sagot :
To find the second derivative of the function \( f(x) = 3 e^{-x^4} \), we can refer to the given second derivative formula:
[tex]\[ f^{\prime \prime}(x) = 12 x^2 \left( 4 x^4 - 3 \right) e^{-x^4} \][/tex]
First, let's find \( f^{\prime \prime}(0) \).
### Finding \( f^{\prime \prime}(0) \):
Substitute \( x = 0 \) into the second derivative:
[tex]\[ f^{\prime \prime}(0) = 12 \cdot 0^2 \left( 4 \cdot 0^4 - 3 \right) e^{-0^4} \][/tex]
Since \( 0^2 = 0 \) and \( e^{-0} = 1 \):
[tex]\[ f^{\prime \prime}(0) = 12 \cdot 0 \cdot \left( -3 \right) \cdot 1 \][/tex]
[tex]\[ f^{\prime \prime}(0) = 0 \][/tex]
So, the correct choice is:
A. \( f^{\prime \prime}(0) = 0 \)
### Finding \( f^{\prime \prime}(1) \):
Next, substitute \( x = 1 \) into the second derivative:
[tex]\[ f^{\prime \prime}(1) = 12 \cdot 1^2 \left( 4 \cdot 1^4 - 3 \right) e^{-1^4} \][/tex]
Calculating inside the parentheses first:
[tex]\[ 4 \cdot 1^4 - 3 = 4 \cdot 1 - 3 = 4 - 3 = 1 \][/tex]
So, it reduces to:
[tex]\[ f^{\prime \prime}(1) = 12 \cdot 1 \cdot 1 \cdot e^{-1} \][/tex]
[tex]\[ f^{\prime \prime}(1) = 12 \cdot e^{-1} \][/tex]
Using the given value of \( f^{\prime \prime}(1) \):
[tex]\[ f^{\prime \prime}(1) = 4.4146 \][/tex]
Thus, the correct choice is:
A. \( f^{\prime \prime}(1) = 4.4146 \)
Therefore, the finalized answers are:
- \( f^{\prime \prime}(0) = 0 \)
- [tex]\( f^{\prime \prime}(1) = 4.4146 \)[/tex]
[tex]\[ f^{\prime \prime}(x) = 12 x^2 \left( 4 x^4 - 3 \right) e^{-x^4} \][/tex]
First, let's find \( f^{\prime \prime}(0) \).
### Finding \( f^{\prime \prime}(0) \):
Substitute \( x = 0 \) into the second derivative:
[tex]\[ f^{\prime \prime}(0) = 12 \cdot 0^2 \left( 4 \cdot 0^4 - 3 \right) e^{-0^4} \][/tex]
Since \( 0^2 = 0 \) and \( e^{-0} = 1 \):
[tex]\[ f^{\prime \prime}(0) = 12 \cdot 0 \cdot \left( -3 \right) \cdot 1 \][/tex]
[tex]\[ f^{\prime \prime}(0) = 0 \][/tex]
So, the correct choice is:
A. \( f^{\prime \prime}(0) = 0 \)
### Finding \( f^{\prime \prime}(1) \):
Next, substitute \( x = 1 \) into the second derivative:
[tex]\[ f^{\prime \prime}(1) = 12 \cdot 1^2 \left( 4 \cdot 1^4 - 3 \right) e^{-1^4} \][/tex]
Calculating inside the parentheses first:
[tex]\[ 4 \cdot 1^4 - 3 = 4 \cdot 1 - 3 = 4 - 3 = 1 \][/tex]
So, it reduces to:
[tex]\[ f^{\prime \prime}(1) = 12 \cdot 1 \cdot 1 \cdot e^{-1} \][/tex]
[tex]\[ f^{\prime \prime}(1) = 12 \cdot e^{-1} \][/tex]
Using the given value of \( f^{\prime \prime}(1) \):
[tex]\[ f^{\prime \prime}(1) = 4.4146 \][/tex]
Thus, the correct choice is:
A. \( f^{\prime \prime}(1) = 4.4146 \)
Therefore, the finalized answers are:
- \( f^{\prime \prime}(0) = 0 \)
- [tex]\( f^{\prime \prime}(1) = 4.4146 \)[/tex]
Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Westonci.ca is your trusted source for answers. Visit us again to find more information on diverse topics.